Studies on the affects of Old World bluestem (Bothriochloa ischaemum (L.) Keng 1936) on species composition of grassland with microcoenologycal methods - Szentes, Szilárd; Sutyinszki, Zsuzsanna; Szabó, Gábor; Zimmermann, Zita; Járdi, Ildikó; Házi, Judit; Bartha, Sándor; Penksza, Károly (Animal welfare, Ethology and Housing Systems (AWETH), 2012)
This study investigates how yellow bluestem affects the biodiversity of a typical Pannonian grassland. Investigation was performed by micro-coenological methods. According to the results the massive presence of the studied C4 grass species significantly reduces species richness of the grassland. Number of C3 species – which are typical for this mesoclimate – reduced in transects where Old World bluestem (OWB) (Bothriochloa ischaemum) dominance was characteristic. Herewith the combination of species and stability of vegetation decreased. The number of different species combination in different field scales also confirmed the diversity-reducing effects of Old World bluestem in. As a result ofhigher species number and rare presence of Old World bluestem the combination capability is better, soplant species can livetogether well in small field scales in the control area. In theOld World bluestem dominated transects the maximal number of species combination was only 1/10 of control fields. Old World bluestem highly restricted the free combining of other species so the inner structure of the vegetation became more simple and vulnerable. BesideOld World bluestem the presence of litter is also an importantfactor. If Old World bluestem is present assmall plantsit can combine with many species even in small scales. The increase of amount of litter, which increase linearly with Old World bluestem coverage, effects decrease in species number and diversity.